Semantic Similarity Implementation for The Circle Application Support Group using Tensorflow Language Models and Scalable Nearest Neighbor - Rizkani, Nadiya; Mardianto, Is; Ariwibowo, Anung Barlianto; Gunawan, M (Penerbitan Universitas Trisakti, 2026)
Mental health is a condition where individuals are free from all forms of symptoms of mental disorders. This project originated from our desire to find solutions to mental health problems in ourselves. It is often difficult to recognize, express, and tell people we know what we feel. Circle is a technology-based mental health application that supports self-help with meditation, support groups, and online counseling with professional psychologists. To make it easier for users to find chat rooms with similar mental health backgrounds in the Support Group, the Support Group search uses full-text matching based on the user-entered subject.